AGROECOLOGICAL PRACTICES AS DETERMINANTS OF SOCIO-ECONOMIC DEVELOPMENT OF FARMERS IN MAKUENI COUNTY, KENYA - MWASEZI MARTHA MAJINA (Machakos University Press, 2025)
Small-scale farmers worldwide are struggling to produce enough food to feed a growing population. Farmers are increasingly being asked to produce in huge quantities while still being ecologically friendly, economically profitable, and socially equitable. Although agroecological practices are increasingly being recognized as sustainable solutions to food insecurity and climate solutions, their adoption in Makueni County remains underexplored in relation to socio-economic development of farmers. Furthermore, financial constraints, weak policy support and inaccessibility to information limits adoption, making it difficult to understand how specific agroecological interventions influence resilience, livelihoods and productivity. Thus, the purpose of this study was to investigate agro-ecological practices as determinants of socio- economic development of farmers in Makueni County, Kenya. Specifically, the study determined the prevalence of agro-ecological practices adopted by farmers, assessed the factors influencing adoption of specific agro-ecological practices and determined the relationship between agro-ecological practices and socio-economic development of farmers. Anchored on Mellor’s Theory of Agricultural Development and the Resource Exploitation Theory, a quantitative research approach and a descriptive cross-sectional design were adopted to explore the study’s objectives. The target population consisted of crop-growing farmers affiliated with 30 self-help groups. To ensure representative sampling, stratification and proportionate sampling techniques were applied to draw participants from a total of 280 farmers. The sample size was determined using a formula provided by Select Statistical Services, resulting in a final selection of 163 respondents. These participants were chosen through proportionate sampling to accurately reflect the broader population under study. To identify the types of agro-ecological practices adopted by farmers, the frequency per item of observed variables was computed while a simple binary logistic regression and simple linear regression was used to examine the factors influencing adoption of specific agro ecological practices and the influence of agro-ecological practices on socio-economic development of farmers, respectively. A total of 87.2% of farmers reported adopting at least one agro-ecological practice, with crop rotation (70.7%) commonly adopted, followed by zero/minimum tillage (51.2%) and agroforestry (43.9%). Whereas, agro ecological practices such as crop residue incorporation (17.7%), legume intercropping (21.3%), compost/manure use (36.6%), cover cropping (23.2%), seed saving (14.6%), planting pest repellant plants (11%), and applying natural pesticides (11.6%) were less widely embraced. Enablers (motivation, accelerator, access to information) and barrier (financial constraints, inadequate extension support, market limitations, cultural and social norms, policy and institutional gaps) factors had a significant effect on the adoption of agro-ecological practices, with motivation showing the strongest positive effect and barriers exerting a strong negative impact. The overall model indicated good fit and moderate to strong predictive power. After regressing the determined agro ecological practices against socio-economic development variable, the study found that agro-ecological practices influence farmers' socio-economic development by around 15.5%. Therefore, agro-ecological practices contribute to socio-economic development of famers by enhancing their livelihoods, improving sustainability and productivity. Motivation, access to information and barriers influence adoption of agro-ecological practices, indicating the need to capacity-build and offer targeted support to encourage sustainable agriculture and foster resilient among farmers.